12
$\begingroup$

Let $a,b,c$ be positive real numbers. Prove that $$\Big({a\over a+b}\Big)^3+\Big({b\over b+c}\Big)^3+ \Big({c\over c+a}\Big)^3\geq {3\over 8}$$

If we put $x=b/a$, $y= c/b$ and $z=a/c$ we get $xyz=1$ and

$$\Big({1\over 1+x}\Big)^3+\Big({1\over 1+y}\Big)^3+ \Big({1\over 1+z}\Big)^3\geq {3\over 8}$$

Since $f(x)=\Big({1\over 1+x}\Big)^3$ is convex we get, by Jensen,: $$\Big({1\over 1+x}\Big)^3+\Big({1\over 1+y}\Big)^3+ \Big({1\over 1+z}\Big)^3\geq 3f({x+y+z\over 3})$$

Unfortunately, since $f$ is decreasing we don't have $f({x+y+z\over 3}) \geq f(1) = {1\over 8}$.

Some idea how to solve this?

$\endgroup$
  • 4
    $\begingroup$ How is this question "seeking personal advice," whoever voted to close this thread? $\endgroup$ – Batominovski Dec 4 '18 at 21:26
6
$\begingroup$

Let $g(t):=\left(\dfrac{1}{1+\exp(t)}\right)^3$ for $t\in\mathbb{R}$. Then, $$g''(t)=\frac{3\,\exp(t)\,\big(3\,\exp(t)-1\big)}{\big(1+\exp(t)\big)^5}\text{ for each }t\in\mathbb{R}\,.$$ Thus, $g$ is convex on $\big[-\ln(3),\infty\big)$.

Let $x:=\dfrac{b}{a}$, $y:=\dfrac{c}{b}$, and $z:=\dfrac{a}{c}$ be as the OP defines. Then, the required inequality is equivalent to $$g\big(\ln(x)\big)+g\big(\ln(y)\big)+g\big(\ln(z)\big)\geq \dfrac{3}{8}\,.\tag{*}$$ If $x$, $y$, or $z$ is less than $\dfrac{1}{3}$, then clearly the left-hand side of (*) is greater than $$\left(\dfrac{1}{1+\frac13}\right)^3=\frac{27}{64}>\frac38\,.$$ If all $x$, $y$, and $z$ are greater than or equal to $\dfrac13$, then $\ln(x),\ln(y),\ln(z)\geq -\ln(3)$, so that we can use convexity of $g$ on $\big[-\ln(3),\infty\big)$. By Jensen's Inequality, $$g\big(\ln(x)\big)+g\big(\ln(y)\big)+g\big(\ln(z)\big)\geq3\,g\left(\frac{\ln(x)+\ln(y)+\ln(z)}{3}\right)=3\,g(0)=\frac{3}{8}\,.$$ Hence, the equality holds if and only if $x=y=z=1$, making $a=b=c$.

$\endgroup$
  • $\begingroup$ I don't get it. What is the difference with my solution? $\endgroup$ – Maria Mazur Dec 4 '18 at 21:45
  • $\begingroup$ I'm not sure what to say to that, but my idea was to bypass the inequality $\frac{x+y+z}{3}\geq \sqrt[3]{xyz}$ that you would need to use in your attempt. $\endgroup$ – Batominovski Dec 4 '18 at 21:48
6
$\begingroup$

This is more of a comment, but I don't have the reputation. Use Lagrange multipliers. Solving, you find that the critical points occur when $xyz=1$ and $yz (1+x)^4 = xz (1+y)^4 = xy (1+z)^4$. I think the only solution is $x=y=z=1$. Clearly, it's a minimum and plugging in shows the bound.

Added:

We can rewrite the condition as $xyz=1$ and $\frac{(1+x)^4}{x} = \frac{(1+y)^4}{y} = \frac{(1+z)^4}{z}$

The function $g(x)=\frac{(1+x)^4}{x}$ is decreasing from $0$ to $1/3$ and increasing from $1/3$ to $\infty$. This shows that 2 of $x,y,z$ must be equal (WLOG $x$ and $y$) and $z=1/x^2$. It remains to solve $\frac{(1+x)^4}{x} = \frac{(1+1/x^2)^4}{1/x^2}$. This time, it's not hard to check $x=1$ is the only solution and we are done.

$\endgroup$
  • 2
    $\begingroup$ It seems to me there's enough here to post as an answer, no need to apologize. $\endgroup$ – David K Dec 4 '18 at 21:11
5
$\begingroup$

By Holder $$\left(\sum_{cyc}\frac{a^3}{(a+b)^3}\right)^2\sum_{cyc}1\geq\left(\sum_{cyc}\sqrt[3]{\left(\frac{a^3}{(a+b)^3}\right)^2\cdot1}\right)^3=\left(\sum_{cyc}\frac{a^2}{(a+b)^2}\right)^3.$$ Thus, it's enough to prove that $$\frac{\left(\sum\limits_{cyc}\frac{a^2}{(a+b)^2}\right)^3}{3}\geq\frac{9}{64}$$ or $$\sum\limits_{cyc}\frac{a^2}{(a+b)^2}\geq\frac{3}{4}.$$ Now, by C-S $$\sum\limits_{cyc}\frac{a^2}{(a+b)^2}=\sum\limits_{cyc}\frac{a^2(a+c)^2}{(a+b)^2(a+c)^2}\geq\frac{\left(\sum\limits_{cyc}(a^2+ab)\right)^2}{\sum\limits_{cyc}(a+b)^2(a+c)^2}.$$ Thus, it's enough to prove that $$4\left(\sum\limits_{cyc}(a^2+ab)\right)^2\geq3\sum\limits_{cyc}(a+b)^2(a+c)^2,$$ which is true even for all reals $a$, $b$ and $c$.

Indeed, the last inequality is symmetric inequality by degree four,

which says that by $uvw$ (https://math.stackexchange.com/tags/uvw/info )

it's enough to prove the last inequality for equality case of two variables and since

it's the homogeneous inequality by even degree, we can assume $b=c=1$, which gives $$(a-1)^2(a+3)^2\geq0.$$ Done!

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.